EVALUASI PROGRAM REMEDIAL MENGGUNAKAN MODEL CONTEXT, INPUT, PROCESS, PRODUCT PADA PEMBELAJARAN FISIKA - Sapira Sapira; Haratua Tiur Maria Silitonga; Syukran Mursyid (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2021)
This research aims to present the evaluation result of a remedial program using the Context, Input, Process, Product (CIPP) model based on Technical Guidance by High School Directorate year 2010 in Physics Study in SMAN 1 Sekadau Hulu. This study is evaluative research with a descriptive quantitative approach. The data collection techniques used are by employing a questionnaire to the students of the MIA (Mathematics and Natural Sciences) Program, interviews with the school principal, deputy head of curriculum, and one teacher of Physics, as well as documentation. The research data analysis is through steps such as data reduction, data presentation, and conclusions. The data validation techniques used are the source and technique triangulation. The findings showed that (1) context evaluation carried out results in a percentage of 74.73%, categorized as sufficient. (2) Input evaluation carried out results in a rate of 56.88%, classified as low. (3) Process evaluation conducted results in a value of 74.07%, categorized as sufficient. (4) Product evaluation administered results in a percentage of 78.70%, categorized as high. The overall score of assessment on the remedial program in Physic instructions using CIPP evaluation is 71,09% with a category corresponding to the technical guidelines for the remedial program by the directorate of high school development year 2010. Therefore, this research is expected to contribute to improvements in remedial programs as a continuous effort in improving the quality of education programs.